Компьютерное моделирование процессов кристаллизации как резерв повышения качества поршней ДВС - Пономаренко, Ольга Ивановна; Тренёв, Николай Сергеевич (Технологічний центр, 2013)
В статье предложено использование процедуры распознавания образов для описания локализации дефектов в литых деталях "поршень" для ДВС. Приведены результаты компьютерного моделирования процесса заполнения кокиля и кристаллизации сплава для усовершенствованной технологии литья, предполагающей применение термоизолирующих покрытий кокиля. Результаты компьютерного моделирования могут быть использованы для формализации процесса описания локализации дефектов в поршнях.

The use of pattern recognition procedure for the description of the localization of defects in the molded pieces "piston" for ICE (internal combustion engine) is proposed in the paper. The relevance of this research is explained by the need of rapid de-velopment of new high quality molded pieces for the automotive industry, or optimization of the existing equipment design to improve the product quality. The results of computer mode ling of the process of metal mold casting and alloy crystallization for the advanced casting technology, involving the use of thermal insulating coatings of metal mold are given. The results of computer modeling can be used for formalization of the process of describing the localization of defects in pistons and, based on this, for development of measures on resource saving and im-proving the quality of molded pieces. It was proposed to use the results of statistical classification on the basis of such formalized description.
Computer modeling of crystallization processes as a reserve of improving the quality of pistons of ICE
Keywords: литая деталь; кокиль; покрытие термоизолирующее; LVMFlow; molded piece; metal mold; computer modeling; thermal insulating coating